SISTEM BACK UP DAYA DAN PENGATURAN KECEPATAN KONVEYOR UNTUK ALAT PEMANEN ROYAL JELLY OTOMATIS - Vira Zafarin; Panca Mudjirahardjo; Eka Maulana (Jurnal Mahasiswa TEUB, 2022)
Royal Jelly is a product produced by honey bees and has many benefits, thus increasing the demand for the product. This high demand is considered not effective because the harvesting system is is carried out using conventional method, by removing one queen cup at a time. If the harvesting process is carried out in large quantities, farmers will have difficulties and this will impact on product quality, because the amount of royal jelly increases within 72 hours, but begins to decrease after 96 hours of larva removal. Therefore, an automatic royal jelly harvester is needed. In this research, the process of designing back up power and setting the conveyor speed. The results of this study, it can be seen that the system is capable of for 30 minutes using an accumulator, when the power goes out. While on the conveyor speed system, the conveyor is able to run at the desired speed according to the in the specified distance range, so that the queen cup object can stop at a position that can be reached by the royal jelly suction for the harvesting process.Keywords: Royal Jelly, Back Up Power System, Duty Cycle, Conveyor